Aplikasi Kompos Ganggang Cokelat (Sargassum polycystum) Diperkaya Pupuk N, P, K Terhadap Inseptisol dan Jagung - Hendra Jawa Sertua; Alida Lubis; Posma Marbun (Jurnal Agroekoteknologi, 2014)
This research aimed to determine the effect of brown algae compost (Sargassum polycystum)enriched with various of dosage N, P and K fertilizer against inceptisol chemical properties andmaize. This research was conducted in June – October 2013 using non-factorial randomized blockdesign, with 7 treatment and 4 replication. That is P0 (not enriched brown algae compost), P1, P2,P3, P4, P5, and P6 (compost enriched urea 2g and 4g dosage level, SP36 2g and 4g dosage level,KCl 0,5g and 1g dosage level). Applied before the vegetative period (when beginning to cultivatethe land) and before the generative period. Parameters measured d canopy, and cob with cornhuskweight. The results showed that brown algae enriched compost significantly affect the pH (H2O),K-exchange soil, plant height and cob with cornhusk. The best dosage is P5 (brown algae compostenriched with urea 4g, SP36 2g, and KCl 0,5g application on early vegetatif and urea 2g, SP36 2g,dan KCl 1g application at the end of vegetative period) against cornhusk cob weight and dry weightof maize plant canopy.Keywords : Brown Algae Compost, N, P dan K Fertilizer, Inceptisol, Maize